2022
DOI: 10.1109/access.2022.3206832
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Character Components Segmentation Method Based on Faster RCNN

Abstract: To solve the component segmentation problem caused by the sticking and overlapping of parts in incoherent handwritten calligraphy characters, we propose a Chinese character part segmentation method based on Faster RCNN. The method utilizes the advantages of Faster RCNN on multi-scale and small targets to solve difficult problems in component segmentation. The hierarchical features of the components were used in our proposed method to identify each layer of the Chinese character structure to obtain the componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Figs. [16][17][18][19] show the writing results and error rates of the characters "永" and "水" using the self-made delta robot.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Figs. [16][17][18][19] show the writing results and error rates of the characters "永" and "水" using the self-made delta robot.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To objectively evaluate the algorithm merits, in addition to the CM-GhostNet-SSD algorithm, five other control groups are set up: the Faster R-CNN algorithm [25], the classical SSD algorithm, the DSSD algorithm [26], the traditional GhostNet-SSD algorithm based on SENet and the modified-GhostNet-SSD algorithm based on ECANet.…”
Section: E Results Analysismentioning
confidence: 99%
“…The DCNN network was also utilized to automatically extract Tangut characters, enabling automated script annotation without manual intervention [12]. Other researchers have explored the use of Convolutional Neural Networks (CNNs) and Recurrent Neural Networks (RNNs), as well as their derivatives such as Region-based CNN (RCNN) [13], Faster RCNN [14], and Bidirectional Long Short-Term Memory (Bi-LSTM) [15], for the recognition of more commonly encountered Chinese characters, including standard Chinese [16] and handwritten forms [17]. Furthermore, previous investigations have suggested that wider convolution networks with larger filters and shallower layers may lead to improved performance [18].…”
Section: Previous Studies Have Employed Deep Convolutionalmentioning
confidence: 99%